Ahmad Subhi Mansur's Thoughts on Hadith Alienation - Siregar, Idris; Sulidar; Faza, Asrar Mabrur (AN NUR: Jurnal Studi Islam, 2025)
Hadith plays an important role in Islamic teachings as an explanation of the Qur'an and a source of Islamic law. However, Ahmad Subhi Mansur's thinking rejects the authority of hadith and asserts that the Qur'an is the only source of Islamic law. Mansur, an academic from Al-Azhar University, developed the idea of ??Quranism which rejects hadith as a valid source of Islamic teachings. He argued that the Qur'an has covered all aspects of human life and does not require additional explanation from hadith. By referring to various verses of the Qur'an, Mansur reinterprets the concept of "rasul" as referring to revelation, not the figure of the Prophet Muhammad personally. This study uses a qualitative method with a literature study approach to analyze Mansur's thinking. Some of the arguments used to reject the authority of hadith include the claim that the Qur'an is perfect, does not require additional laws, and the prohibition of following anything other than the Qur'an. Mansur's thinking has caused controversy and is contrary to the views of the majority of scholars who accept hadith as an integral part of Islamic teachings. This study aims to understand the basis of Ahmad Subhi Mansur's thinking, his method of interpretation, and the implications of his ideas for the study of hadith and Islamic law.